The Effect of Fear of the COVID-19 on Depression Among Chinese Outbound Students Studying Online in China Amid the COVID-19 Pandemic Period: The Role of Resilience and Social Support - Chen, Yikang; Liu, Yifan; Zhang, Yuxuan; Li, Zheng; Zhou, Tianshu (Frontiers in Psychology, 2021)
Objective: The present study focused on examining whether fear of COVID-19 is correlated with depression, and explored the potential role of resilience and social support on the association between fear of COVID-19 and depression, among Chinese outbound students studying online in China amid the COVID-19 pandemic. Methods: A total of 476 Chinese outbound students from different universities worldwide, currently studying via online mode in China, completed an online survey including measures on fear of COVID-19, resilience, social support and depression. Results: (1) Fear of COVID-19 was positively correlated with depression, and negatively correlated with resilience and social support. Both resilience and social support were negatively correlated with depression. Social support showed a positive correlation with resilience. (2) The effect of fear of COVID-19 on depression mainly occurred through two paths: the mediating effect of resilience and the moderating effect of resilience. However, the moderating effect of social support on the association between FoC and depression was not sustained in this study. Conclusion: This study indicated the mediating and moderating effects of resilience on the association between fear of COVID-19 and depression among Chinese outbound students studying online in China during the COVID-19 pandemic. The current finding confirmed that resilience has significant implications in preventing negative mental states under the COVID-19 context among this particular group.